Going under to stay on top: How much real exchange rate undervaluation is needed to boost growth in developing countries - Bermúdez, Cecilia; Dabús, Carlos (Estudios de Economía, 2018)
This paper explores the real exchange rate (RER)-economic growth relationship for a wide sample of countries over the period 1960-2009. After removing influential observations, the system-GMM estimates suggest a positive link between an undervalued RER and growth in non-industrial countries, particularly in those with upper-middle and high income levels. In turn, RER volatility is found harmfulfor growth. These results holds when testing for asymmetric effects of RER misalignment: a real undervaluation boosts growth in non-industrial countries, while overvaluation seems to have no effects at any income level. Besides, the magnitude of the misalignment is also relevant: an undervalued RER of about 26% on average has a positive impact on growth.